Connettivi tedeschi e poeticità: l'attivazione dell'interprete tra forma e funzione Studio teorico e analisi di un caso esemplare - Ballestracci, Sabrina (Biblioteca di Studi di Filologia Moderna, 2019)
Connettivi tedeschi e poeticità: l'attivazione dell'interprete tra forma e funzione. Studio teorico e analisi di un caso esemplare. Starting from Jakobson's definition of poeticalness, the volume studies the mechanisms by which connectors, such as linguistic signs assigned to the connection between parts of speech, contribute to the poeticalness in a text, which is here intended as a textual peculiarity capable of activating the interpreter in the tout court language, but mainly in the literary text. The first two chapters of this volume offer an overview of the theoretical and methodological foundations that justify the choice to acquire the connectors as possible indicators of poeticalness, and also a preparatory introduction to the third chapter, where there is the description of the results from a study on the syntax and semantics of the connector in in a collection of German poetry texts from the first half of the 20th century.